Survey on Big Data Acquisition tools and techniques - Arockia Jaya J, Dr. Mahalakshmi K (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In the past years, word big data have been used for labelling attributes by various players. Also, various methods to process architectures for big data were given to meet the various features big data. Altogether, data acquisition is known as the method to gather, filter, as well as clean data prior to storing the data in a data warehouse or any other solutions for storing. The location of big data acquisition among the overall big data value chain are depicted in Fig. 1. Obtaining big data is very often decided by 4 Vs: volume, velocity, variety, and value. Many data obtaining scenarios provide high-volume, high-velocity, high-variety, yet low-value data, that made it of utmost importance to get adapted as well as time-efficient gathering, filtering, and cleaning algorithm which makes sure that specifically high-value parts of the data usually underwent processing by the data-warehouse analysis. Still few organizations, many data are of more value so that it could be of utmost importance to get new consumers. For such organization, data analyzing, classifying, and packing on a increased data capacities that provide the maximum central role post data obtaining.